Juegos coordinativos en los movimientos básicos defensivos del baloncesto en niños. - Sislema Huerta, Nanci Jhoanna (2025)
The present research work titled "Coordinative Games in Basic Defensive Movements of Basketball in Children" aims to develop coordinative skills and basic defensive basketball movements in children from the Unidad Educativa Fernando Daquilema, promoting their physical, technical, and tactical abilities to improve their athletic performance. As a data collection method, the 3JS Test was used—a set of physical assessments developed to measure specific motor skills in athletes. The methodology applied in this research is both descriptive and propositional, as it not only focuses on analyzing and describing the influence of coordinative games on basic defensive basketball movements but also on proposing strategies to optimize their application in training sessions. This design seeks to improve children's defensive performance. The research is classified as quasi-experimental, as it focuses on data collection before and after the intervention through a pre-test and post-test design. This approach allows for measuring the effects of implementing coordinative games on the improvement of basic defensive movements in children who practice basketball, without the need for random assignment of participants. The results obtained show that this methodology enhances motor responses, body stability, and anticipation during the game—key factors for efficient defensive performance